A frequency domain equalizer for amplify-and-forward underwater acoustic relay communication systems - Nguyen, K.; Rong, Yue; He, Z. (IEEE, 2013)
In this paper, we apply the amplify-and-forward relay technique to simultaneously increase the range and data rate of underwater acoustic communication by dividing the channel between transmitter and receiver into two hops. Due to the application of the relay node, the delay spread of the effective transmitter-relay-receiver multipath channel is longer than that of the direct transmitter-receiver channel, which increases the complexity of channel equalization at the receiver. To reduce the computational complexity of channel equalization, a fractionally-spaced frequency domain equalizer (FS-FDE) isdesigned in this paper. Simulation results illustrate that compared with the direct path communication, significant bit-error-rate performance improvement can be achieved through using relay technique in underwater acoustic communication.